ESG disclosure and firm performance before and after IR: The moderating role of governance mechanisms - Albitar, Khaldoon; Hussainey, Khaled; Kolade, Nasir; Gerged, Ali Meftah (International journal of accounting and information management, 2020)
PurposeThis paper aims to investigate the effect of environmental, social and governance disclosure (ESGD) on firm performance (FP) before and after the introduction of integrated reporting (IR) further to exploring a potential moderation effect of corporate governance mechanisms on this relationship.Design/methodology/approachOrdinary least squares and firm-fixed effects models were estimated based on data related to FTSE 350 between 2009 and 2018. The data has been mainly collected from Bloomberg and Capital IQ. This analysis was supplemented with applying a two-stage least squares (2 SLS) model to address any concerns regarding the expected occurrence of endogeneity problems.FindingsThe results show a positive and significant relationship between ESGD score and FP before and after 2013, among a sample of FTSE 350. Furthermore, the study is suggestive of a moderation effect of corporate governance mechanisms (i.e. ownership concentration, gender diversity and board size) on the ESGD-FP nexus. Additionally, this paper finds that firms voluntarily associated with IR have a tendency to achieve better firm financial performance.Practical implicationsThe findings of the present study have several policy and practitioner implications. For example, managers may engage in ESGD to enhance their firms’ financial performance by the voluntary involvement in IR, which believed to help investors to rationalise their investment decisions. Likewise, the results reiterate the crucial need to integrate more social, environmental and economic regulations to promote sustainability in the UK. The paper also offers a systematic picture for policymakers in the UK as well as future researchers.Social implicationsThe findings of this paper indicate that IR plays a significant role in the relationship between ESGD and FP, where IR firms seemed to be achieving better FP as compared with their non-IR counterparts. This implies that stakeholders may have played a magnificent effort to encourage firms’ voluntary engagement in IR in the UK.Originality/valueTo the best of the authors’ knowledge, this is the first study to explore the potential moderating effect of ownership concentration, gender diversity and board size on the relationship between ESGD and FP and to examine whether firms’ voluntary involvement in IR can lead to better FP after the introduction of IR in 2013 in the UK.